2020
DOI: 10.2337/dc20-1663
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Rates of Continuous Glucose Monitor Initiation and Continued Use in Children With Type 1 Diabetes

Abstract: OBJECTIVE Racial/ethnic disparities in continuous glucose monitor (CGM) use exist among children with type 1 diabetes. It is not known whether differential rates of device initiation or sustained use are the cause of this disparity. Our objective was to compare CGM initiation rates and continued use among non-Hispanic White (NHW), non-Hispanic Black (NHB), and Hispanic children. RESEARCH DESIGN AND METHODS We conducted a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 12 publications
2
58
0
Order By: Relevance
“…19,20 Nonetheless, exclusion of non-CGM users may yield a unique subsample given the recognized disparities in diabetes technology use. [21][22][23] We recognize that our study sample may reflect a more advantaged group of individuals by virtue of their overall use of advanced diabetes technologies and their ability to access telehealth during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Nonetheless, exclusion of non-CGM users may yield a unique subsample given the recognized disparities in diabetes technology use. [21][22][23] We recognize that our study sample may reflect a more advantaged group of individuals by virtue of their overall use of advanced diabetes technologies and their ability to access telehealth during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…We defined two subgroups, youth (ages 13-18) and young adult (ages [19][20][21][22][23][24] in this cohort study. We calculated the diabetes-related hospitalization rates and evaluated the differences in demographic characteristics between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high prescription drugs costs may reduce insulin adherence and even lead to discontinuation of insulin therapy. An increasing number of studies have shown that use of technology devices, such as pump and CGM, are significantly impacted by the insurance types (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Future work should explore the perceptions of male youth, fathers, nontechnology users, and more diverse ethnic samples, as much research shows disparities in technology use for ethnic minorities. [32][33][34] Youth and parents primarily desired an AP system that would reduce physical burdens and mental efforts associated with self-care through a discreet, user-friendly system with personalized algorithms and settings. Stakeholders should be encouraged that young persons with T1D and parents recognize and welcome the potential of AP systems to reduce burden, even without full automation.…”
Section: Many Of the Features Described By Participants Are Currently Avail-mentioning
confidence: 99%